Video-based interviewing in medicine: a scoping review - Selvam, Rajajee; Hu, Richard; Musselman, Reilly; Raiche, Isabelle; McIsaac, Daniel I.; Moloo, Husein (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background The Coronavirus 2019 pandemic necessitated a rapid uptake of video-based interviewing within the personnel selection process in healthcare. While video-based interviews have been evaluated previously, we identified a gap in the literature on the implementation of video-based interviews and how they compare to their face-to-face counterparts. Methods A scoping review was conducted to consolidate the available literature on the benefits and limitations of video-based interviews and to understand the perceived barriers associated with transitioning away from face-to-face interviews. A search strategy, developed in concert with an academic health sciences librarian, was run on Ovid MEDLINE, Embase, PsycInfo, and Cochrane Central. The search was performed on March 31, 2020, and updated on February 21, 2021. Studies that implemented and evaluated the impact of video-based interviewing in healthcare were included in our study. Review articles and editorials were excluded. Results Forty-three studies were included in our scoping review, of which 17 were conference abstracts and 26 were peer-reviewed manuscripts. The risk of bias was moderate or high in most studies, with only four studies having a low risk of bias. Both financial costs and opportunity costs associated with the selection process were reported to be improved with video-based interviewing, while no studies explored the impact on environmental costs. Technical limitations, which were not prevalent, were easily managed during the interview process. Overall, video-based interviews were well received by both applicants and interviewers, although most participants still reported a preference for face-to-face interviews. Conclusions While video-based interviewing has become necessary during the Coronavirus 2019 era, there are benefits from a financial, opportunistic, and environmental point of view that argue for its continued use even after the pandemic. Despite its successful implementation with minimal technical issues, a preference still remains for face-to-face interviews. Reasons for this preference are not clear from the available literature. Future studies on the role of nonverbal communication during the video-based interview process are important to better understand how video-based interviewing can be optimized. Systematic review registration This scoping review was registered with Open Science Framework.